Sporidesmiella motuoensis, a new freshwater fungus from Tibetan Plateau, China - Xiong, Yu-Chun; Xu, Rong-Ju; Luo, Zong-Long; Gao, Qian; Zhao, Qi (Phytotaxa, 2024)
During an investigation of freshwater fungi in the Tibetan Plateau, China, a new hyphomycetous fungus, Sporidesmiella motuoensis, was isolated from submerged decaying wood in freshwater habitat. Sporidesmiella motuoensis is characterized by cylindrical, straight or slightly flexuous conidiophores, hyaline, smooth conidiogenous cells, and obovoid, hyaline to pale brown, 3-euseptate conidia. Phylogenetic analyses of combined ITS and LSU sequence data indicated that S. motuoensis formed a highly supportive monophyletic lineage within Sporidesmiella. A full description, illustrations, and phylogenetic analyses results of S. motuoensis, along with comparisons to other affinities within Sporidesmiella are provided here.